Microstructural evolution and mechanical properties of ultra-fine grained tubular components processed by severe plastic deformation / Mohsen Mesbah - Mohsen , Mesbah (2020)
The lightweight alloys have been widely used in various engineering applications such as automotive, aerospace, construction, and biomedical industries due to their low densities, high ductility, formability, and facile machining. However, the emerging trend for materials with high mechanical strength and plasticity hampers the widespread application of these alloys. Over the last two decades, severe plastic deformation (SPD) has been introduced as a promising approach for enhancement of the mechanical performance of the lightweight alloys through microstructural manipulations and grain refinement. However, the SPD techniques have been extensively utilized for the fabrication of non-tubular geometries and the studies on the manufacturing of ultra-fine-grained tubular components using SPD methods are scarce. The present research aims to study the microstructural evolution and mechanical properties of Al-1060, Brass70/30, ZK60, and WE43 Mg alloys processed by different SPD methods including tubular channel angular pressing (TCAP) and parallel tubular channel angular pressing (PTCAP). Accordingly, the main objective of this study is to investigate the possibility of fabricating ultrafine-grained (UFG) alloys via TCAP and PTCAP techniques and explore the effects of the number of passes on microstructural evolution and mechanical properties of the SPD-processed alloys as compared with the as-received counterparts. Several characterization techniques, such as X-ray diffraction (XRD) analysis, optical microscope (OM), scanning electron microscope (SEM) combined with energy-dispersive X-ray spectroscopy (EDS), electron back-scattered diffraction (EBSD), transmission electron microscopy (TEM), and mechanical tests were employed to investigate the microstructural and mechanical characteristics of UFG alloys. The obtained results confirmed the formation of homogeneous UFG structures with the minimum number of passes of 1 for Al and brass, as well as 3 for ZK60 and WE43. The minimum mean grain sizes obtained in TCAP-processed Al, as well as PTCAP-processed brass, ZK60 and WE43 were 0.48 μm, 0.59 μm, 0.9 μm, and 2.2 μm respectively. It was proposed that dynamic recrystallization as well as breaking and distributing of the precipitates at the newly-formed grains were the dominant phenomena after the SPD processes. The X-ray diffraction (XRD) profiles also confirmed the significant effect of the number of SPD passes on the microstructural characteristics of all four studied alloys. In terms of the mechanical properties, the hardness of the processed tubes increased and reached a maximum by increasing the number of SPD passes. The different SPD processes enhanced not only strength but also the ductility of the tubular component due to the simultaneous fine grain strengthening mechanism and homogeneous distribution of the intercomponent metallics in the alloy matrix. As a conclusion, the studied SPD processes exhibited significant potentials to generate UFG structures, leading to enhanced mechanical properties in the Al-1060, Brass70/30, ZK60, and WE43 Mg alloys.